Efektivitas Model Inkuiri Terbimbing Berbasis STEM untuk Meningkatkan Kemampuan Berpikir Kritis Siswa pada Materi Laju Reaksi : Literature Review - Siti Jabaria Anwar; Astin Lukum; Thayban Thayban; Masrid Pikoli; Erga Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This study is a literature review aimed at examining the effectiveness of the guided inquiry model based on STEM in enhancing students’ critical thinking skills. The guided inquiry model provides a structured framework for students to explore problems under teacher guidance, while the STEM (Science, Technology, Engineering, and Mathematics) approach promotes interdisciplinary, contextual, and practical learning. Through an analysis of various relevant articles and scholarly journals, the findings indicate that the implementation of the guided inquiry model integrated with STEM consistently improves students' critical thinking abilities, particularly in areas such as analysis, evaluation, and reasoning. The study also highlights the crucial role of teachers as active facilitators in the learning process and the need for adequate resources to effectively apply this approach. The results of this review are expected to serve as a reference for educators and researchers in developing innovative and 21st-century-oriented learning strategies.